The answers you are looking for are x = 6 and y = 4.
For these 2 equations, you would subtract the second one into the first one. This is so the y's cancel out temporarily, and so we can solve for x.
(10x + 3y = 72) - (9x + 3y = 66) = (x = 6).
Now, to find the y value, you take 6 and fill it in for x in one of the equations. I chose to use (10x + 3y = 72). The equation now says 10 * 6 + 3y = 72.
10 * 6 = 60. (60 + 3y = 72)
60 - 60 = 0 and 72 - 60 = 12. (3y = 12)
3y ÷ 3 = y and 12 ÷ 3 = 4 (y = 4)
Thus meaning your answers are x = 6 and y = 4. Here's a photo to show how i solved it as well.
I hope this helps!